PROFICIENT IN PLANNING OF SUPPLY EVENTS STAFFING REQUIREMENTS (American Journal of Interdisciplinary Research and Development, 2026)
This article is devoted to the development of the process of managing the educational process of higher education based on a creative approach to planning technical support activities.